Ethical Moderation on Framing Relationships, Audit Tenure and Compliance Pressure on Audit Judgment - Heni Suryanti; Muhammad Nur (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study examines and analyzes the impact of framing, audit tenure, and obedience pressure on audit judgment at KAP in South Jakarta, with auditor ethics as a moderating variable. This study's population consists of independent auditors employed by public accounting firms registered with IAPI who reside or work in one of five KAPs in South Jakarta. The sampling method utilized purposive sampling with the following criteria: 1) Senior auditors and 2) Auditors who have worked for more than five years; thus, the total sample size is 80 auditors. This study utilizes primary data collected by distributing questionnaires to all respondents containing multiple statements with four answer options, each of which will be assigned a weighted score (Strongly Agree = 4, Agree = 3, Disagree = 2, Strongly Disagree = 1). The collected data will undergo multiple testing phases before being analyzed. The analysis method employs the Structural Equation Model (SEM) and the Smart PLS application to analyze technical data. Our findings indicate that Framing and audit tenure has a positive and statistically significant effect on audit judgment. In contrast, obedience pressure negatively and statistically significantly affects audit judgment. These findings suggest that the greater the auditor's pressure, the less precise or reduced their audit judgment. An auditor subjected to intense obedience pressure from superiors and the entity being audited will tend to behave safely and provide a poor and inaccurate judgment. Auditor ethics can moderate the impact of framing and audit tenure on audit judgment but not the impact of obedience pressure. This indicates that auditor ethics, as a moderating variable, diminishes the effect of obedience pressure on audit judgment. When under pressure from the client or his superiors, an auditor is likelier not to perform some of the necessary auditing procedures.